2018
DOI: 10.1097/gox.0000000000001881
|View full text |Cite
|
Sign up to set email alerts
|

Squid Ring Teeth–coated Mesh Improves Abdominal Wall Repair

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Histological staining showed moderate inflammatory response and prominent collagen deposition anterior to the SRT-PP mesh, which was corroborated by increased ultimate strength. But there were no elastin staining or quantification revealed that the SRT-PP mesh is less stiff (more elastic) than the PP mesh . Especially, the SRT-PP mesh tends to form the stiff collagen-rich scar with the encapsulation of undegraded PP other than the mature connective tissue after remodeling.…”
Section: Functional Meshesmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological staining showed moderate inflammatory response and prominent collagen deposition anterior to the SRT-PP mesh, which was corroborated by increased ultimate strength. But there were no elastin staining or quantification revealed that the SRT-PP mesh is less stiff (more elastic) than the PP mesh . Especially, the SRT-PP mesh tends to form the stiff collagen-rich scar with the encapsulation of undegraded PP other than the mature connective tissue after remodeling.…”
Section: Functional Meshesmentioning
confidence: 99%
“…But there were no elastin staining or quantification revealed that the SRT-PP mesh is less stiff (more elastic) than the PP mesh. 46 Especially, the SRT-PP mesh tends to form the stiff collagen-rich scar with the encapsulation of undegraded PP other than the mature connective tissue after remodeling. The investigation of the mechanics of SRT-biologic mesh is expected in further study.…”
Section: Functional Meshesmentioning
confidence: 99%
“…(b) Pre-coating and (c) post-coating images show a homogeneous coating around individual polypropylene fibers. Reproduced with permission (Leberfinger et al, 2018). (d) Multilayer biomolecule encapsulation (enzymes), providing built-in detection and protection against hazardous agents.…”
Section: Srt Based Films In Textile Applicationsmentioning
confidence: 99%
“…This hard biological material is mainly composed of a group of semicrystalline proteins ranging from 18 to 55 kDa in size. Recently, SRT proteins from diverse species have been sequenced, enabling the analysis of their amino acid sequence and the heterologous expression of recombinant and synthetic SRT proteins in host organisms (e.g., genetically modified Escherichia coli bacteria). , Because of their outstanding physical properties (mechanical, thermal, conducting, etc. ), these squid proteins and their bioengineered derivatives (recombinant and synthetic proteins) are finding applications in biological and nonbiological applications, from medical devices , to biophotonic sensors and flexible electronics . Recent research efforts have shed light on the role of amino acid composition, nanostructure, and network topology on the physical properties of novel SRT-inspired proteins.…”
Section: Introductionmentioning
confidence: 99%